Combining Lithium Isotope Systematics, Stable Isotopes, and Major Elements as a Powerful Tool for Detection of the Slab-Dehydrated Fluids in Southwestern Japan - Rofiqul Umam (Indonesian Journal on Geoscience, 2026)
This research aims to obtain a very sensitive geochemical analysis method to detect the contribution of thermal water or slab-dehydrated fluids to the surface waters of the Arima hot spring water in southwestern Japan. In this study, four groundwater samples from the previous research in the form of lithium isotope systematics and chlorine were taken from the public baths of the Arima hot spring waters. In addition, fourteen Arima hot water samples in the form of stable isotope and major element data of fourteen Arima hot water samples from previous research were also used. The interpretation of lithium isotopes (δ7Li) and Cl/Li ratios shows that four groundwater samples in this study have a δ7Li < 5 ‰ and Cl/Li < 1,000 and are in the thermal water category. Meanwhile, thirteen Arima hot spring waters from the previous research do not have lithium isotope (δ7Li) data and might be able to be estimated based on Li > 0.1 lmg/l, Cl > 1,000 lmg/l, and Cl/Li < 1000 and are in the thermal water category. One of the Arima hot spring waters from the previous research is a mixing water category with fairly high Cl, namely 435 mg/l. The combinations of lithium isotope systematics, stable isotopes, and major elements might be useful as a powerful geochemical analysis for the detection of slab-dehydrated fluids.